Analisis Sistem Antrian Sepeda Motor Untuk Meningkatkan Efektivitas Pelayanan Pada Stasiun Pengisian Bahan Bakar Umum (SPBU) 14.214.280 Simpang Mangga Rantauprapat - Nasution, Aldi; Kurniawan, Juliardi; Rambe, Boby Pratama; Hasibuan, Mustapa Ali; Ritonga, Irmayanti (Universitas Labuhanbatu, 2025)
This research aims to analyze the motorbike queuing system at the Simpang Mangga Rantau Prapat Public Fuel Filling Station (SPBU) with a focus on increasing service effectiveness. Long and irregular queues have led to long waiting times, which has a negative impact on customer satisfaction. Through evaluating the performance of the existing queuing system, this research identified several causal factors, including a surge in visitors during peak hours and an imbalance between the number of customers and service capacity. As a solution to overcome this problem, this research proposes several strategies, including optimizing the queuing system using the Multi Channel Single Phase (M/M/S) model, adding service lanes, and diverting vehicle lanes during peak hours. The results of this research show that implementing these strategies can increase customer satisfaction and operational efficiency of gas stations. With better queue management and the application of technology, it is hoped that the customer experience can be improved, and a positive impact on traffic around gas stations can be achieved.